Microelectronic design of fuzzy logic-based systems. ([2018?]) - Baturone, I (Iluminada); Díaz Barriga, Ángel; Sánchez-Solano, Santiago; Jiménez-Fernández, Carlos J; Lopez, Diego R
No abstract available